OVERVIEW OF STUDENT STRESS IN FOLLOWING DISTANCE LEARNING SYSTEM - Ni Putu Diah Kusumasari; Ni Made Nopita Wati; Ni Luh Putu Devhy (Jurnal Sains Kesehatan, 2021)
Students who in the future are expected to be able to become professional nurses with good abilities since college. Students are also expected to have good and logical thinking. The excessive stress that an individual has will largely determine the quality of the behavior he displays, both in study, work and in other lives. Stress consists of 2 sources, namely internal stress sources and external stress sources. Research objectives This study aims to describe the stress of students in following the distance learning system. Methods: This study uses a descriptive method. The technique used is total sampling with a sample of 150 respondents. Collecting data using a distance learning stress questionnaire with a Likert scale. Results: The results showed that most of the students had a very heavy internal stress source as much as 67.5% and a very heavy external stress source as much as 89.4%. Nursing students for the most part have great stress in following the distance learning system. The results of this study are expected to be input for finding solutions in overcoming sources of stress faced by nursing students in undergoing distance learning